Pharmacological screening of silibinin for antischizophrenic activity along with its acute toxicity evaluation in experimental animals - Ain, Qurat Ul; Saleem, Uzma; Ahmad, Bashir; Khalid, Iqra (Frontiers in Pharmacology, 2023)
Silibinin (SIL), a flavolignan extracted from the medicinal plant “silybum marianum (milk thistle)”, has traditionally been used to treat liver disease. This phytochemical has displayed neuroprotective properties, its activity against schizophrenia is not elucidated. The present study was designed to evaluate the antipsychotic potential of silibinin and probe its toxic potential. The acute oral toxicity study was assessed as per OECD 425 guidelines. Animals were divided into two groups of female rats (n = 6): one group served as the normal control and the other group received a 2,000 mg/kg dose of SIL. We also evaluated the antipsychotic potential of SIL. To this end, animals were divided into six groups (n = 10) of mice for both the preventive and curative protocols. Group I (CMC 1 mL/kg) served as the normal control and received CMC 1 mL/kg; group II was the diseased group treated with ketamine (10 mg/kg) i.p; group III was the standard group treated with clozapine 1 mg/kg; groups IV, V, and VI served as the treatment groups, receiving SIL 50, 100, and 200 mg/kg, respectively, orally for both protocols. Improvement in positive symptoms of the disease was evaluated by stereotypy and hyperlocomotion, while negative symptoms (behavioral despair) were determined by a forced swim test and a tail suspension test in the mice models. The results suggested that the LD50 of SIL was greater than 2,000 mg/kg. Moreover, SIL prevented and reversed ketamine-induced increase in stereotypy (p < 0.001) and behavioral despair in the forced swim and tail suspension tests (p < 0.001). Taken together, the findings suggest that silibinin is a safe drug with low toxicity which demonstrates significant antipsychotic activity against the positive and negative symptoms of schizophrenia.